Combined anti-PD-L1 and anti-VEGFR2 therapy promotes the antitumor immune response in GBM by reprogramming tumor microenvironment - Lin Yao; Hao Wang; Yongsheng Liu; Ming Feng; Yanyan Li; Zuopeng Su; Wen Li; Yun Xiong; Heyang Gao; Youxin Zhou (Cell Death Discovery)
Abstract Inhibitors of programmed cell death ligand 1 (PD-L1) and vascular endothelial growth factor receptor 2 (VEGFR2) are commonly used in the clinic, but they are beneficial for only a minority of glioblastoma multiforme (GBM) patients. GBM has significant immunosuppressive properties, and there are many immunosuppressive cells and dysfunctional effector T cells in the tumor microenvironment (TME), which is one of the important reasons for the failure of clinical treatment of GBM. Here, we have identified P21 activated kinase 4 (PAK4) as a pivotal immune suppressor in the TME. PAK4 is a threonine protein kinase, and PAK4 knockdown attenuates vascular abnormalities and promotes T-cell infiltration. In this study, our results showed that the expression of PAK4 was significantly downregulated after VEGFR2 knockdown. Next, we constructed a coculture system of CD8+ T cells and GBM cells. Our findings showed that combined anti-PD-L1 and anti-VEGFR2 therapy can regulate the TME and inhibit GBM cells' immune escape; overexpression of PAK4 can reverse this effect. Finally, we tested the combination therapy in mouse intracranial graft tumor models and found that combination therapy can prolong mouse survival. These findings suggest that anti-VEGFR2 therapy can downregulate PAK4, reprogram the TME by increasing cytotoxic CD8+ T cells infiltration and activation, and enhance the therapeutic effect of anti-PD-L1 therapy on GBM cells.